Fra ‘Interkulturelle kompetencer’ til et intersektionelt blik – Om socialarbejderes sans for arabisktalende mødres positioner - Nanna Brink Larsen (The Royal Danish Library, 2006)
The article argues that ‘intercultural’ social work could fruitfully be oriented towards the intersectional backgrounds of minority- (as well as majority-)Danish clients. In addition, it has to be based on an approach to intersectionality that emphasises the context-specific and unpredictable articulation of different category positions. Hence, rather than aiming at the acquisition of ‘intercultural competences’ in the sense of transferable, generalisable knowledge of the Other’s cultural dispositions, development projects in ‘intercultural’ social work could work from a more open set of questions concerning the differentiality of positions that make a difference in specific contexts. As ‘culture’ is indeed a category that strongly influences our frameworks of interpretation this may take the meta-competence of observing the influence of one’s own preconstructed articulations of e.g. Arabicness with other categories and with specific problem versions.